Hybridization and introgression of native and foreign Sorbus tree species in unique environments of protected mountainous areas. Issue 1 (30th December 2020) - Hebda, Anna; Kempf, Marta; Wachowiak, Witold; Pluciński, Bartosz; Kauzal, Paweł; Zwijacz-Kozica, Tomasz
Abstract: Hybridization and introgression are important processes influencing the genetic diversity and evolution of species. These processes are of particular importance in protected areas, where they can lead to the formation of hybrids between native and foreign species and may ultimately result in the loss of parental species from their natural range. Despite their importance, the contribution of hybridization and introgression to genetic diversity in Sorbus genus remains not fully recognized. We analysed the genetic and morphological variability of several Sorbus species including native ( Sorbus aria ), foreign ( S. intermedia ) and potentially hybrid ( S. carpatica ) individuals from the Polish Carpathian range. Patterns of variation at 13 nuclear microsatellite loci show hybridization between the tested species and confirm the existence of the hybrid form S. carpatica . Biometric analysis on leaves, based of 10 metric features and three parameters, identified several characters for preliminary taxonomic classification; however, none of them could be used as a fully diagnostic marker for faultless annotation of S. intermedia and S. carpatica . The genetic structure analysis indicated complex patterns of population differentiation and its diverse origin. The results allow assessment of genetic variation and identification of parental species participating in hybridization. This knowledge will advance the management of genetic diversity and development of conservation strategies for efficient maintenance of the unique protected ecosystem. Abstract : Hybridization, polyploidization and apomixis are important processes which affect the taxonomic complexity of Sorbus genus. The phenomenon of interspecific hybridization between native and foreign species is frequently a consequence of human activity. It may lead to increased diversity of plants but also it may significantly reduce genetic variation if invasive genotypes of natural species participate in the process. We report a preliminary study of the hybrid taxon occurring in natural and protected areas of Tatra National Park in Poland. Variation patterns at nuclear microsatellite loci were used to distinguish a hybrid form of Sorbus carpatica from morphologically very similar S. intermedia .